2011
DOI: 10.3109/02713683.2011.573898
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Thymoquinone on Ovalbumin-induced Allergic Conjunctivitis in Balb/c Mice

Abstract: Administration of TQ significantly reduced the ocular symptoms in AC by attenuating the recruitment of eosinophils, level of IgE, histamine and cytokines. Our findings suggest that TQ might be a useful intimation for the treatment and future research for AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
15
0
5
Order By: Relevance
“…In a study that implemented TQ application in conjunctivitis treatment, it was reported that, in addition to other immunity parameters, Ig E level decreased as well (Hayat et al, 2011). Anti-inflammatory properties of TQ on rats with asthma were proven by demonstrating its detractive effect on serum Ig E (Ammar et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In a study that implemented TQ application in conjunctivitis treatment, it was reported that, in addition to other immunity parameters, Ig E level decreased as well (Hayat et al, 2011). Anti-inflammatory properties of TQ on rats with asthma were proven by demonstrating its detractive effect on serum Ig E (Ammar et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The important function of oxidative stress in the pathophysiological process of liver injury and fibrosis induced by biliary occlusion is one of the most studied aspects of cholestatic liver injury treatment (Khorasani et al, 2008;Hayat et al, 2011). Previous studies (LaLonde et al, 1997;Konishi et al, 2006;Nagi et al, 2010) show that model rats with bile duct ligation have pathological features similar to those of human cholestatic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…No earlier work evaluated the effect of thymoquinone in allergic rhinitis, but a few studies on its effects on other allergic diseases have been published [8,9,10,11,12]. Besides, thymoquinone has a very low toxicity, and a few cases of contact dermatitis have been reported after its use; otherwise, no adverse effects are listed [21].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that thymoquinone exerts anti-inflammatory effects in patients with certain allergic diseases, including asthma, food allergies, and allergic conjunctivitis [8,9,10,11,12], but its effect on allergic rhinitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%